Messenger roles of extracellular vesicles during fertilization of gametes, development and implantation: Recent advances - Fan, Weisen; Qi, Yinghua; Wang, Yaqian; Yan, Huiting; Li, Xuan; Zhang, Yingjie (Frontiers in Cell and Developmental Biology, 2023)
Extracellular vesicles (EV) have become a research hotspot in recent years because they act as messengers between cells in the physiological and pathological processes of the human body. It can be produced by the follicle, prostate, embryo, uterus, and oviduct in the reproductive field and exists in the extracellular environment as follicular fluid, semen, uterine cavity fluid, and oviduct fluid. Because EV is more stable at transmitting information, it allows all cells involved in the physiological processes of embryo formation, development, and implantation to communicate with one another. EVs carry mirnas and proteins as mail, and when the messenger delivers the mail to the recipient cell, the recipient cell undergoes a series of changes. Current research begins with intercepting and decoding the information carried by EVs. This information may help us gain a better understanding of the secrets of reproduction, as well as assist reproductive technology as an emerging marker and treatment.